The Effect of Ginger (Zingiber officinale var. Rubrum) Administration on Pregnant Women with Emesis Gravidarum - Syamsiah, Siti; Carolin, Bunga Tiara; Putri, Meidy Regita (GLOBAL HEALTH SCIENCE GROUP, 2024)
Emesis gravidarum, a common complaint among pregnant women in the first trimester, affects 70-80% of pregnancies, often presenting as morning sickness. If untreated, it can escalate to hyperemesis gravidarum, posing risks to pregnancy. Ginger, a herbal remedy, has been traditionally used to alleviate nausea and vomiting. Objective to investigate the influence of ginger (Zingiber officinale var. Rubrum) administration on pregnant women experiencing emesis gravidarum at the Depok Clinic. This study employed a quasi-experimental research design, specifically the One Group Pretest-Posttest Design. The sample comprised 34 first-trimester pregnant women at the Depok Clinic, selected through total sampling. Data collection involved observation, with participants given 2.5 grams of sliced ginger brewed in 250 ml of hot water and sweetened with 10 grams of sugar, to be consumed twice daily for four days. Emesis gravidarum was assessed using Validity refers to whether an instrument (such as the PUQE-24) accurately measures the intended concept—in this case, the symptoms of emesis gravidarum. Validity assessment involves examining whether the data obtained from the instrument aligns with the true underlying phenomenon being studied. Data analysis included univariate and bivariate analyses using the Paired T-Test. Reliability can be observed by assessing how consistently the emesis scores obtained before and after the ginger intervention are. If the scores show consistent patterns or changes, it indicates good reliability. Before the ginger intervention, the average emesis score was 10.74, with the majority falling into the moderate nausea and vomiting category, constituting 76.5% of the sample. After the ginger intervention, the average emesis score decreased to 6.88, with the majority still experiencing moderate nausea and vomiting, comprising 52.9% of the participants. These findings suggest that administering ginger (Zingiber officinale var. Rubrum) to mothers with emesis gravidarum has a significant effect. The efficacy of ginger in reducing emesis gravidarum has been demonstrated.